Geometric possibility - Belot, Gordon (Oxford : Oxford University Press, 2011)
Relationalism seeks to ground all claims about the structure of space in facts about actual and possible configurations of matter. Gordon Belot elucidates the prospects for this view of the nature of space by investigating the kew notion of geometric possibility in relation to philosophical notions of physical possibility.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Space and time; Relationism